A brief profile of laryngeal lesions undergoing microlaryngeal surgery by telescopic method - K S Gangadhara; S Ramesh; Gayatri Jayan; Shubham Malawadi; Jerin Alex (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Telescopic-assisted Microlaryngeal surgery (MLS), also known as video laryngoscopic surgery, is increasingly becoming popular because of the ease of the technicalities. Magnification and the improved delicacy of instrumentation help us in differentiating the extent of the lesion and performing a precise cutting out. MATERIALS AND METHODS: Forty-seven patients presented to our tertiary health center and underwent MLS by the telescopic method are taken into consideration for the present study. RESULTS: Among 47 patients who underwent surgery by telescopic method, males were predominant, and majority were in the 51-60 years of age group. A total of 19 were benign, 8 were premalignant, and 20 were malignant. Majority of the cases involved the middle third of the vocal cord and only two cases involved the posterior third of the vocal cord. All benign lesions were subjected to speech therapy, and malignant lesions were immediately sent for radiotherapy and no recurrence was noted on regular follow-up. DISCUSSION: It is easy to expose the larynx and we have never faced any difficulty in exposure of the vocal cord lesion. Delineation of the tissue in terms of morphology, site of lesion, and vascularity was very precise. Instrumentation was unimpeded, and documentation was easy. CONCLUSIONS: We conclude that the telescopic-assisted MLS is the better modality to deal with the lesions of vocal cords.